PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MENULIS TEKS FABEL SISWA KELAS VII SMP NEGERI 4 PAYAKUMBUH - Ermawati Arief, Tiara Fitma, Erizal Gani, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This study has three objectives as follows. (1) Describe the skills of writing fabel text class VII students of SMP Negeri 4 Payakumbuh before using bassed learning problem model. (2) Describe the skills of writing fabel text class VII students SMP Negeri 4 Payakumbuh after using the model problem bassed learning. (3) To describe the influence of problem based learning model on the skill of writing fabel  text of class VII students of SMP Negeri 4 Payakumbuh. Next Model Problem Based Learning abbreviated as PBL. This research type is quantitative research with experiment method. The design of this study using a group of subjects students class VII SMP Negeri 4 Payakumbuh registered in 2016-2017 which amounted to 329 people. The sample of this research is the students of grade VII.1 SMP Negeri 4 Payakumbuh which determined by using purposive sampling technique with certain consideration. The variable of this research is the skill of writing fabel text before and after using model of PBL of student of class VII of  SMP Negeri 4 Payakumbuh. Kata kunci: pengaruh, model problem based learning, menulis teks fable